Pendekatan Pencegahan dan Penanggulangan Banjir Melalui Program Kuliah Kerja Nyata di Desa Lewotobi Kecamatan Ile Bura - Maria M.K Kwuta; Daniel Wolo; Helena Rosalia Parera; Ana Maria Gadi Djou (Jurnal Pengabdian kepada Masyarakat Radisi, 2021)
Lewotobi village has great potential to improve the economy of its people. The potential consists of two, namely natural resources and human resources. Lack of knowledge and lack of motivation cause the existing potential has not been utilized optimally. In addition, there are problems encountered in the community, such as low awareness and participation from residents, especially young people, to participate in community service activities in the environment, and there are no ditches for drainage of rainwater so that some residents' houses are submerged in water during the rainy season. The empowerment model that is carried out to the community is a form of a participatory approach. This service activity involves the community, especially young people, to advance their village. Parents and village government assisted by facilitating capacity-building activities such as training tour guides.